2016
DOI: 10.1186/s13287-016-0339-7
|View full text |Cite
|
Sign up to set email alerts
|

Sphere-forming cells from peripheral cornea demonstrate the ability to repopulate the ocular surface

Abstract: BackgroundThe limbus forms the outer rim of the cornea at the corneoscleral junction and harbours a population of stem cells for corneal maintenance. Injuries to the limbus, through disease or accidents such as chemical injuries or burns, may lead to significant visual impairment due to depletion of the native stem cells of the tissue.MethodsSphere-forming cells were isolated from peripheral cornea for potential use as transplantable elements for limbal stem cell repopulation and limbal reconstruction. Immunoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 40 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…This original report and additional studies by independent laboratories have confirmed the presence of ABCB5+ LSC in human and mouse limbal epithelium. [48][49][50][51][52][53] Moreover, our most recent studies utilizing genetic lineage tracing in Abcb5/Cre reporter mice crossed with tdTomato [B6;129S6-Gt(ROSA)26Sor tm14(CAG-tdTo mato)Hze /J] mice, 54 aimed at further dissecting the origin of LSC and their progeny cell fate, identified tdTomato-positive ABCB5-derived progeny within the entire adult mouse corneal epithelium (Figure 2), identifying at the level of genetic lineage tracing an ABCB5-expressing precursor cell that gives rise to self-renewing corneal epithelium during development and regeneration, consistent with the LSC phenotype.…”
mentioning
confidence: 99%
“…This original report and additional studies by independent laboratories have confirmed the presence of ABCB5+ LSC in human and mouse limbal epithelium. [48][49][50][51][52][53] Moreover, our most recent studies utilizing genetic lineage tracing in Abcb5/Cre reporter mice crossed with tdTomato [B6;129S6-Gt(ROSA)26Sor tm14(CAG-tdTo mato)Hze /J] mice, 54 aimed at further dissecting the origin of LSC and their progeny cell fate, identified tdTomato-positive ABCB5-derived progeny within the entire adult mouse corneal epithelium (Figure 2), identifying at the level of genetic lineage tracing an ABCB5-expressing precursor cell that gives rise to self-renewing corneal epithelium during development and regeneration, consistent with the LSC phenotype.…”
mentioning
confidence: 99%
“…24,62 Limbal ESC obtained from young donors may produce better stem cells for clinical therapies. 63 Sphere forming cells are also a promising cell type for stem cell repopulations 30,64 and native LNC may promote the expansion of LEPC. 19 Human corneal stromal SC may survive in stored organ or culture, 26 although biomechanics exhibit a powerful effect on LNC and their growth and differentiation.…”
Section: Endothelial Progenitor Cells and The Stem Cell Nichementioning
confidence: 99%
“…Even if the limbal cells themselves were abated, cells from the central cornea would move towards the limbal area to fill the void that had been created. Taking this data in conjunction with the data above, we then decided to examine the migration properties of the peripheral corneal spheres when transplanted back onto a denuded corneal stroma and adjacent limbus [15].…”
Section: Figurementioning
confidence: 99%